EFFECT OF GENERATION Y ENGAGEMENT WITH FACEBOOK BRAND PAGES ON ONLINE SALES IN SRI LANKAN CONTEXT - Madhusanka, K. T. G. P. (University of Jaffna, 2019)
With the development of new technologies, competition within industries are rising, and marketers are finding new ways to persuade customers to spend money on their brands. As social network sites have become increasingly important in customers' lives, this new trend has done business to realize that if they wish to reach their prospects and customers, their online presence in social network sites is a foundation of their overall marketing strategy. Brand pages on social network sites have become the key platform where customers interact with brands, and therefore, the key objective of this study is to examine how the customer engagement with Facebook brand pages effect on online sales of a business. Further, the study investigates what the mediation effect of brand awareness on the relationship between customer engagement and online sales is. The study proposed a research model that examines in what manner the three levels of customer engagement (consumption, contribution, and creation) can contribute to the online sales of a brand and how the brand awareness mediates this relationship, empirically testing the model using 195 respondents. Structural equation modeling technique was used for the data analysis, and the results confirmed that consumption level engagement has a direct effect on online sales, consumption, and creation levels have a direct effect on brand awareness, and no mediation effect was found in the study.
Keywords: brand awareness; brand pages; customer engagement; generation y; online sales